Study of Humanistic Learning with The Among Approach to Improve Teacher Performance at The Lumajang Regency Education and Culture Office - Agus Salim; I Nyoman S Degeng; Punaji Setyosari; Made Duananda Kartika Degeng; Henry Praherdhiono (Jurnal Indonesia Sosial Teknologi, 2024)
This research aims to explore the effectiveness of the humanistic learning approach with the Among method in improving teacher performance in the Lumajang Regency Education and Culture Office. The humanistic approach, which puts students at the center of the learning process, is expected to increase teacher involvement, motivation, and competence in managing the classroom and developing student potential. The research method used is a qualitative case study, with data collected through in-depth interviews, participatory observations, and document analysis. The results showed that the Among approach significantly improved teachers' performance in terms of creativity, emotional engagement, and managerial ability. The study also identified some limitations and provided recommendations for further research. In conclusion, the application of humanistic learning with the Among method can be an effective model for improving teacher performance and education quality in Lumajang Regency.